2014
DOI: 10.1515/pjap-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of Self-Perception Profile for Children in a Polish sample

Abstract: Abstract:The Self-Perception Profile for Children (SPPC) is a measure which allows one to assess children's self-concept. Our article presents this instrument's psychometric properties within a Polish sample. In our study we tested 432 elementary school students and 14 form teachers. As validity indicators we used the Teacher's Rating Scale of Child's Actual Behavior (TRS) and the average school grade for the previous semester. The Polish version of SPPC yielded good psychometric properties. The instrument's f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
5
0
1
Order By: Relevance
“…One explanation for the lack of age-related differences observed in the present study may relate to the fact that the UK is a more developed country than Brazil, with different social and health contexts. However, when it comes to agerelated differences in self-concept, data from the present study concur with previous work, with children becoming more self-critical about their physical features and social abilities as they reach adolescence [45,61].…”
Section: Discussionsupporting
confidence: 91%
“…One explanation for the lack of age-related differences observed in the present study may relate to the fact that the UK is a more developed country than Brazil, with different social and health contexts. However, when it comes to agerelated differences in self-concept, data from the present study concur with previous work, with children becoming more self-critical about their physical features and social abilities as they reach adolescence [45,61].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, perceptions of global self-worth may not have been properly formed in the current age groups studied. Also, the studies of Harter (2005) and Gacek et al (2014) have shown that, in many different cultures, at the stages of life at which the present children were at global self-worth has the strongest relationship with perceived physical appearance, and not with evaluations of personal scholastic and athletic competence. This may also explain the present lack of change in children's global self-worth under the influence of money priming.…”
Section: Discussionmentioning
confidence: 85%
“…Children were randomly assigned to either an experimental group (n = 43) or a control group (n = 40). In a first part of the experiment, children in the experimental group were primed with money and those in the control group were given an equivalent non-monetary treatment, while in a second part of the study all participants completed the Self-Perception Profile for Children (SPPC;Harter 1985;Gacek et al 2014). The experimental manipulation was conducted in groups of 10 to 15 children and based on the procedure used in the studies of Gąsiorowska et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations